A novel rare c.-39C>T mutation in the PROS1 5′UTR causing PS deficiency by creating a new upstream translation initiation codone. Issue 10 (29th May 2020) - Labrouche-Colomer, Sylvie; Soukarieh, Omar; Proust, Carole; Mouton, Christine; Huguenin, Yoann; Roux, Maguelonne; Besse, Céline; Boland, Anne; Olaso, Robert; Constans, Joël; Deleuze, Jean-François; Morange, Pierre-Emmanuel; et al.
Abstract: Autosomal dominant inherited Protein S deficiency (PSD) (MIM 612336) is a rare disorder caused by rare mutations, mainly located in the coding sequence of the structural PROS1 gene, and associated with an increased risk of venous thromboembolism. To identify the molecular defect underlying PSD observed in an extended French pedigree with seven PSD affected members in whom no candidate deleterious PROS1 mutation was detected by Sanger sequencing of PROS1 exons and their flanking intronic regions or via an multiplex ligation-dependent probe amplification (MLPA) approach, a whole genome sequencing strategy was adopted. This led to the identification of a never reported C to T substitution at c.-39 from the natural ATG codon of the PROS1 gene that completely segregates with PSD in the whole family. This substitution ACG→ATG creates a new start codon upstream of the main ATG. We experimentally demonstrated in HeLa cells that the variant generates a novel overlapping upstream open reading frame (uORF) and inhibits the translation of the wild-type PS. This work describes the first example of 5′UTR PROS1 mutation causing PSD through the creation of an uORF, a mutation that is not predicted to be deleterious by standard annotation softwares, and emphasizes the need for better exploration of such type of non-coding variations in clinical genomics.